2007
DOI: 10.1016/j.juro.2006.10.075
|View full text |Cite
|
Sign up to set email alerts
|

Video Endoscopic Inguinal Lymphadenectomy: A New Minimally Invasive Procedure for Radical Management of Inguinal Nodes in Patients With Penile Squamous Cell Carcinoma

Abstract: Video endoscopic inguinal lymphadenectomy is a safe and feasible technique in patients with penile carcinoma and nonpalpable nodes. These preliminary results suggest that video endoscopic inguinal lymphadenectomy may decrease postoperative morbidity without compromising oncological control. Future studies should include the bilateral procedure, longer term followup and a greater number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 17 publications
6
60
0
3
Order By: Relevance
“…Contemporary series show that refinements of the technique during surgery associated with adequate postoperative care can decrease complication rates to approximately 50% [26,27]. Recently, Tobias-Machado et al [28] reported preliminary results suggesting that video endoscopic inguinal lymphadenectomy might decrease postoperative morbidity without compromising oncological control. Dynamic sentinel node biopsy has been used for patients with node negative T2-T3 penile carcinoma, however this technique has been associated with a false-negative rate of 16% (6 of 37 patients) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary series show that refinements of the technique during surgery associated with adequate postoperative care can decrease complication rates to approximately 50% [26,27]. Recently, Tobias-Machado et al [28] reported preliminary results suggesting that video endoscopic inguinal lymphadenectomy might decrease postoperative morbidity without compromising oncological control. Dynamic sentinel node biopsy has been used for patients with node negative T2-T3 penile carcinoma, however this technique has been associated with a false-negative rate of 16% (6 of 37 patients) [29].…”
Section: Discussionmentioning
confidence: 99%
“…This can be related to the devascularization of skin flaps, the disruption of lymphatic afferents, concomitant medical conditions that predispose to poor wound healing, and simultaneous septic operative steps as ablation of a potential necrotic and infected primary tumor. Since the first description of an endoscopic approach by Bishoff in 2003 [16], Tobias-Machado et al have published a consistent comparison with the open procedure on the same patient [17,[23][24][25][26] demonstrating a significant reduced morbidity for the video-assisted approach (70% versus 20%) [23][24][25]. Other published series have consistently reported fewer skin postoperative events and lymphatic morbidity [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Video endoscopic inguinal lymphadenectomy (VEIL) also has developed as a minimally invasive approach for LND in penile SCC although data are limited by small numbers of patients [27]. While not routinely performed at our institution, VEIL has shown some promising improvements in patient morbidity after LND [28].…”
Section: Discussionmentioning
confidence: 99%